2019
DOI: 10.1007/jhep03(2019)204
|View full text |Cite
|
Sign up to set email alerts
|

Improved bounds on ℤ3 singlet dark matter

Abstract: We reconsider complex scalar singlet dark matter stabilised by a Z 3 symmetry. We refine the stability bounds on the potential and use constraints from unitarity on scattering at finite energy to place a stronger lower limit on the direct detection cross section. In addition, we improve the treatment of the thermal freeze-out by including the evolution of the dark matter temperature and its feedback onto relic abundance. In the regions where the freeze-out is dominated by resonant or semi-annihilation, the dar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 97 publications
1
34
0
Order By: Relevance
“…For earlier studies involving different aspects of Z 3 symmetric DM, see, for example, refs. [44][45][46][47][48][49][50]. The effective low-energy interaction Lagrangian involving the χ and the φ particles is given by…”
Section: Numerical Resultsmentioning
confidence: 99%
“…For earlier studies involving different aspects of Z 3 symmetric DM, see, for example, refs. [44][45][46][47][48][49][50]. The effective low-energy interaction Lagrangian involving the χ and the φ particles is given by…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This has been done recently in the context of DM freeze-out in [31,32], where it has been also shown that solving the system of equations for coupled 0-th and 2-nd moment (cBE) of (4.1) instead often gives from fairly to very good estimate of the resulting relic density. 4 At the same time the structure of the semi-annihilation and semi-production rates is technically more challenging due to the necessity of performing thermal averages on pairs of particles with different temperatures [14,15,33]. Having all this in mind we therefore leave full numerical solution of (4.1) to future work, while here we focus on the system of cBE.…”
Section: Boltzmann Equationsmentioning
confidence: 99%
“…Note that the BR inv can exclude points with m χ > m h /2, because the Higgs boson can decay invisibly also to two h 2 if it is light enough. Early kinetic decoupling [92,93] may additionally enhance BR inv several times [31], but in practice this would not change the parameter space of GW signals. In particular, all our points with a potentially measurable GW signal have m χ , m 2 > m h /2.…”
Section: Direct Detection and Gravitational Wave Signalsmentioning
confidence: 99%
“…The cubic coupling can contribute to 3 → 2 scattering for Z 3 strongly interacting (SIMP) DM [27][28][29][30]. The effects of early kinetic decoupling were studied in [31]. The Z 3 symmetry has been considered as the remnant of a dark U (1) local [32][33][34] or global [35] symmetry.…”
Section: Introductionmentioning
confidence: 99%